The role of oxidative damage in poor scalp health: ramifications to causality and associated hair growth. (December 2015) - Schwartz, J. R.; Henry, J. P.; Kerr, K. M.; Mizoguchi, H.; Li, L.
Abstract: The oxidative stress element of unhealthy scalp leads to compromised pre‐emergent hair formation and poorly formed hair as it grows. Only cosmetic solutions can minimize the impact of unhealthy hair and to achieve healthy looking and feeling hair, the scalp health must be normalized first. The objectives of this research were to both investigate whether oxidative stress was a relevant aetiological element in scalp dandruff and seborrhoeic dermatitis and whether scalp condition affects the quality of hair that grows from it. Further, this research was designed to determine whether an effective anti‐dandruff shampoo would repair and protect the scalp and pre‐emergent hair from oxidative stress. This study demonstrated that oxidative stress is an aetiological element relevant to the dandruff condition and that a potentiated ZPT shampoo effectively improves scalp condition, including a reduction in oxidative stress. The compromised hair condition associated with dandruff is concomitantly improved when the scalp condition is improved. It appears that there is a direct link between hair quality and scalp health.